Relationship between the evaluation of the teaching performance in the learning of the mathematics area of the students of the V cycle of regular basic education of the educational institution Nº3071 Manuel García Cerrón - Puente Piedra district - Ugel 04 - Saga Lipa, Máximo (2020)
Scientific research we have done is basic causal correlational experimental variables of the study are twofold: Teacher performance assessment and learning in thE area of?? mathematics. the population consisted of 506 students and 16 professors’ the sample by 233 students and 8 teachers. The research design is transactional, correlational, causal. bivariate cross. For data collection produced two structured questionnaires as measurement and consists of two aspects: On the teacher evaluation will take into account the following: Responsibility teaching, planning, assessment and teaching resource. As area learning mathematics take into account the following indicators: Number, relationships and operations, geometry and measurement as well as statistics. The study proposes the following. There is a relationship between the teacher performance assessment with learning area Mathematics students of the V cycle Basic Education of School District No. 3071 Stone Bridge hypothesis: By applying the formula of Spearman Rho with a significance level of 95% found that the correlation coefficient Spearman's rho = 0.686 and 0.000 p_ value is therefore establish that it has a good correlation level, we see that there is a relationship direct significance level less than 0.05 we can add that to apply linear regression found that the variable teacher performance assessment dependent influence on the learning of mathematics by 41.4% as it has an R squared of 0.414 for this reason we reject the Null hypothesis and accept the alternative.